Prohibited-use trees species at the Campus Rodrigo Facio, University of Costa Rica: a landscape proposal for its conservation - Flores, Laura Chaverri (2021)
In the world, there is a latent loss of tree species affecting ecosystems. In Costa Rica, the prohibition decrees that ban the exploitation of some species of trees are the first actions taken by the State to try to save them from their possible extinction. The general objective of this article is to analyze the prohibited-use species in Costa Rica located at Rodrigo Facio campus. Methodologically, an inventory took place at this site that identified all native trees and their respective spatial location in plans, including banned-use species. An analysis was elaborated for each of these species, based on legislation, background, and bibliographic sources. As results found, of the eighteen species of prohibited-use trees, six are located on this campus: five classified as critically endangered, and one as a vulnerable species. A map was developed with their respective location, alongside landscape management recommendations. An analysis of each species was carried out according to its ecologicalimportance, phenology, design characteristics, and use given at the university, plus a map of these species with their natural distribution in the botanical regions of Costa Rica. In conclusion, these trees are part of the university's natural heritage, where the dissemination of their importance should be promoted, along with a landscape protection plan. The study of these species is fundamental to make decisions for territorial planning of both the university and the country.